ABILITY OF STUDENTS IN MEDIA USE IN PRACTICE LEARNING EXPERIENCE IN THE FIELD II MADRASAH IBTIDAIYAH MUHAJIRIN BANJARMASIN - salmah, syarifah (Universitas Islam Negeri Antasari Banajarmasin, 2017)
Learning media is an important factor in improving the quality of learning. In connection with the use of media in the learning process, teaching staff need to be careful in the selection of media that will be used. This study aimed to describe the use of a medium of learning by students on field practice II in Al-Muhajirin Government Elementary School Banjarmasin. Data collected by observation. The analysis used is descriptive qualitative approach. Based on the results of the study illustrated the ability of PPL student in utilizing instructional media included in either category that most or some 63.6% of the students can use the media in accordance with the general principles of the use of media. Key Words: Media Learning, Practice Fields II